SERVICE MANAGEMENT ANALYSIS AT KING STYLE BARBERSHOP TO IMPROVE CUSTOMER SATISFACTION - Nadya Ernada; Asrindah Nasution; Sri Mulyani (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
This study aims to analyze service management at King Style Barbershop to improve customer satisfaction. A descriptive qualitative approach was used, with data collection techniques including in-depth interviews, participant observation, and analysis of online review documentation. The study involved eight informants, including the owner, employees, and customers. The results were analyzed based on the five dimensions of SERVQUAL (tangibles, reliability, responsiveness, assurance, and empathy). The findings indicate that King Style Barbershop has successfully implemented good service management, particularly in the areas of tangibles, responsiveness, and assurance. Cleanliness, comfortable premises, and friendly employee interactions are key factors in customer satisfaction. However, there is still variation in service consistency (reliability) between barbers and uneven levels of personalization (empathy), especially when customers are served by different barbers. The implications of this study provide strategic recommendations in the form of developing consultation SOPs, a customer preference recording system, implementing online bookings, and ongoing training to consistently and sustainably improve service standards.